BUILDING CHARACTER IN EARLY CHILDHOOD THROUGH ISLAMIC-BASED MEDIA FOR LEARNING - Jf, Nurul Zahriani (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to explore and implement a learning approach for positive character development in early childhood. Through the development of learning media with Islamic values, this research to create a fun and educational learning environment for children. for children. The research method uses a qualitative approach with a case study as the as the main design. Data were collected through observation, interviews and analysis of analysis of documents related to the use of Islamic-based learning media. Islamic-based learning media. The research findings show that Islamic-based learning media in Islamic-based learning media in Yayasan Peduli Kasih (YPK) as an early childhood education institution consisting of RA, PG, and TPA, which consists of RA, PG and TPA, proved to be not only a supporting has proved to be not only a supportive tool, but also a key player in shaping the character of early childhood. The Foundation as a whole has succeeded in Islamic-based learning media holistically, not only for academic aspects, but also for shaping early childhood character, for academic aspects, but also for shaping Islamic attitudes and values. Therefore, the results of this study show that the Islamic-based educational media approach can be used as an effective model for early childhood character development. Islamic-based learning media can be used as an effective model for early childhood character development with positive implications that can be adopted by other early childhood education institutions other early childhood education institutions.